2014
DOI: 10.1002/hed.23789
|View full text |Cite
|
Sign up to set email alerts
|

T3‐T4 laryngeal cancer in The Netherlands Cancer Institute; 10‐year results of the consistent application of an organ‐preserving/‐sacrificing protocol

Abstract: There were no differences in survival according to T classification or treatment modality. Because the majority of T3 laryngeal cancers were treated with (C)RT and the majority of T4 with total laryngectomy + RT, this gives food for thought on whether the present protocol for T3 laryngeal cancer is optimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 30 publications
(67 reference statements)
10
55
1
5
Order By: Relevance
“…Since most T3 LSCC in our cohort was treated non-surgically by radiotherapy or chemoradiotherapy, and the majority of T4a surgically by TLAR and postoperative radiotherapy (50 Gy), these findings merit attention. Our results are consistent with a study from the Netherlands concerning 10-year outcomes following organ-sparing versus organ-sacrificing management of T3-T4 laryngeal cancer [22]. Timmermans and co-workers found no significant difference in five-year OS between T3 LSCC (primarily treated by radiotherapy or chemoradiotherapy) and T4 LSCC (primarily treated by TLAR).…”
Section: Discussionsupporting
confidence: 92%
“…Since most T3 LSCC in our cohort was treated non-surgically by radiotherapy or chemoradiotherapy, and the majority of T4a surgically by TLAR and postoperative radiotherapy (50 Gy), these findings merit attention. Our results are consistent with a study from the Netherlands concerning 10-year outcomes following organ-sparing versus organ-sacrificing management of T3-T4 laryngeal cancer [22]. Timmermans and co-workers found no significant difference in five-year OS between T3 LSCC (primarily treated by radiotherapy or chemoradiotherapy) and T4 LSCC (primarily treated by TLAR).…”
Section: Discussionsupporting
confidence: 92%
“…Timmermans et al (2015) also restaged their patients, but reported only on 5-year overall survival (51% for RT and 61% for CCRT) because information about the cause of death in their retrospective database was judged unreliable by the authors. 24 Patient eligibility criteria are another issue, both while applying different non surgical treatments and regarding the debate among surgical and non surgical treatment options. There seems to be no consensus on the indications of ChRT versus RT alone with the use of either one seeming to rely on empirical parameters, such as the rough estimation of tumor bulk.…”
Section: Populationmentioning
confidence: 99%
“…From a total of 635 larynx cancer patients treated at the Netherlands Cancer Institute between January 1999 and December 2008, 182 patients had biopsy‐proven T3 or T4 larynx cancer and were treated with curative intent with RT, CCRT, or TL + PORT, as extensively described earlier . Patient‐ and treatment‐specific data collected included age, sex, American Society of Anesthesiologists score for comorbidity (ASA score), TNM classification, subsite, treatment, local and regional recurrences, distant metastases, and survival status.…”
Section: Methodsmentioning
confidence: 99%
“…This was an unexpected finding because generally T3 tumors are considered to have a better prognosis than T4 disease, when corrected for nodal status. That the majority of T3 larynx cancers were treated with RT or CCRT and the majority of T4 with TL (± PORT) was a possible explanation for this finding . In that study, all cases were uniformly restaged (based on the available radiology reports) according to the latest (seventh) UICC edition, because the classification has changed over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation